Phylogenetic analysis of Dengue-2 serotypes circulating in mangroves in Northern Cordoba, Colombia (2019)
ABSTRACT: Introduction: In this study, we aimed to identify DENV-2 subtypes in Aedes aegypti pools collected between 2011 and 2017 in a rural area of Northern Cordoba, Colombia (“La Balsa”). Methods: RT-PCR was performed to analyze the capsid/pre-membrane region (C-PrM). Sequencing and phylogenetic bayesian inference using reference DENV-2 sequences were performed. Results: Twelve pools that tested positive for DENV-2 were characterized based on the C-PrM region and grouped under the Asian/ American clade. Conclusions: This study is the first to report the DENV-2 Asian-American subtype in a rural area of Cordoba region, which is associated with severe dengue and local epidemics.